Effect of sulphur on uptake of major plant nutrients in rapeseed in soils of NEH region of India - Saiborne, Ian Borney; Lenka, N K (Annals of Agricultural Research, 2016)
An experiment was conducted using soils from two soil series, Nongpoh and Umsoing (Umsning) of Meghalaya, collected from different land uses, with rapeseed as test crop in the Rabi season of 2008-09. The objective of the experiment was to study the effect of S application on uptake of major nutrients, such as N, P and K in rapeseed plants. Four levels of S (0, 20, 40 and 60 mg S kg-1 soil) were taken for the study. The data from the pot experiment showed that S uptake increased with increase in level of S application even up to 60 mg S kg-1 soil, and the effect was significant in most of the study sites. The increase in S uptake resulted significantly higher N, P and K uptake up to the level of 40 mg S kg-1 in most of the soils studied. Highly significant and positive correlation (r = 0.639** to 0.973**) was observed between uptake of S and that of other nutrients, viz., N, P and K, indicating a synergistic effect among these nutrients.